Optimization of donor structure enhances the generation of cloned goats with high expression of human butyrylcholinesterase by CRISPR/Cas9 - Wu, Yunpeng; Zheng, Jianhua; Chen, Jingqing; Sun, Tianqi; Luan, Tianqi; Li, Yan; Fa, Yunzhi; Qiu, Yefeng; Zhang, Rui (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionHuman butyrylcholinesterase (hBChE) is a promising bioscavenger against organophosphorus (OP) nerve agents and pesticides. However, low homology-directed repair (HDR) efficiency in CRISPR/Cas9-mediated genome editing limits precise transgene integration in large animals.MethodsTo improve HDR, we optimized donor structure for targeted integration of hBChE into the goat FGF5 locus using CRISPR/Cas9. Correctly edited goat fibroblast clones were identified by PCR and sequencing. A homozygous clone with reverse-oriented integration was used as a donor for somatic cell nuclear transfer (SCNT), followed by embryo transfer. Offspring were analyzed for genomic integration and transgene expression.ResultsReverse-oriented donors significantly enhanced HDR efficiency compared to forward designs, with validation at the pig RAG1 locus. Edited cells stably expressed recombinant hBChE (rhBChE) and showed increased resistance to OP pesticides. SCNT produced a cloned goat expressing high rhBChE levels in the skin.DiscussionOptimizing donor structure improves precise genome editing efficiency and enables robust generation of transgenic goats. This strategy advances CRISPR/Cas9-based bioreactor development for scalable production of therapeutic proteins.